A new oncoplastic technique with immediate nipple reconstruction for central breast tumors using Würinger's septum-based flap. Issue 10 (October 2022) - Hamdi, Moustapha; Marina, Cristina; De Baerdemaeker, Randy; Kapila, Ayush K.; Vanhoeij, Marian; Giunta, Gabriele; Zeltzer, Assaf
Abstract: Introduction: Centrally located breast tumors represent a challenge for both oncological and reconstructive surgeons, mainly due to the necessity of nipple-areola complex (NAC) removal. We describe an original oncoplastic solution utilizing a displacement flap technique with immediate nipple reconstruction. Methods: Since 2008, we developed an oncoplastic technique using a septum-based island flap for the reconstruction of central breast defects, including the NAC. This technique is based on the Würinger's septum which is centered around the intercostal perforators. A retrospective study was performed collecting data on patient characteristics, oncological features, and outcomes. Patient satisfaction was reported using a Likert scale. Results: Reconstruction was successfully realized in 15 patients (14 immediate and one delayed post-lumpectomy correction). In immediate surgery, the excision margins were all free of tumor. Minor complications occurred in three patients; one small area of skin necrosis was managed by secondary intention, and two cases of partial nipple necrosis were treated by debridement under local anesthesia. Contralateral symmetrization surgery was performed on nine patients. Patient satisfaction scored high. Conclusion: In comparison with the previous oncoplastic techniques used for reconstructing central defects, the septum-based island flap has increased flexibility, provides better projection, and can be combined with immediate NAC reconstruction.